2013
DOI: 10.1007/s00404-013-3079-2
|View full text |Cite
|
Sign up to set email alerts
|

Emergency peripartum hysterectomy: our 12-year experience

Abstract: In our series, abnormal placentation was the most common indication for EPH. The risk factors for EPH were previous CS for abnormal placentation and placental abruption for uterine atony and peripartum hemorrhage. Limiting the number of CS deliveries would bring a significant impact on decreasing the risk of EPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 33 publications
2
35
0
3
Order By: Relevance
“…This is consistent with the findings of previous studies, which reported placenta accreta and uterine atony as the most common causes of hemorrhage leading to peripartum hysterectomy [21][22][23]. Previous cesarean delivery did explain a substantial fraction (37.6 %) of severe PPH, signaling the presence of placentation abnormalities.…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with the findings of previous studies, which reported placenta accreta and uterine atony as the most common causes of hemorrhage leading to peripartum hysterectomy [21][22][23]. Previous cesarean delivery did explain a substantial fraction (37.6 %) of severe PPH, signaling the presence of placentation abnormalities.…”
Section: Discussionsupporting
confidence: 94%
“…[4][5][6][7][8][9][10][11] In the face of unremitting hemorrhage, obstetricians face a dilemma: perform the procedure (balancing risks of surgery and possible desire of the woman to preserve fertility) or delay while attempting other therapies that may result in severe morbidity or death. Availability of blood transfusion and other interventions (eg, uterotonic agents, B-Lynch sutures, and arterial embolization) may have reduced need.…”
Section: Methods Of Study Selectionmentioning
confidence: 99%
“…Interstudy heterogeneity was assessed using x 2 test for heterogeneity. 1,[4][5][6]9,10,[91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110] Two studies were analyzed as one (same sample), 4,113 so the total number of papers was considered 128. Pooled odds ratio (OR) with 95% CI was calculated for categorical variables.…”
Section: Study Selectionmentioning
confidence: 99%
“…Placenta previa accreta-a life-threatening condition complicated by massive hemorrhage during parturition [17][18][19][20]-affected 14 women in the present study. Cesarean hysterectomy is often required to control bleeding in women with placenta previa accreta [21,22]. Eleven of the women with placenta previa accreta in the present study underwent cesarean hysterectomy.…”
Section: Discussionmentioning
confidence: 87%